Laboratory assay measurement of modified clotting factor concentrates: a review of the literature and recommendations for practice. (17th February 2019) - Young, Guy A.; Perry, David J.
Abstract : Summary: Over the past several years, novel modified clotting factor concentrates (CFCs) have been introduced into practice and are now widely prescribed in the countries where they are licensed. These products allow for less frequent infusions of CFC, thereby providing improved convenience and/or higher trough levels. They have been extensively studied for prophylaxis, episodic treatment of bleeding and for surgical prophylaxis. One issue that has emerged regarding the clinical application of these products revolves around the measurement of infused CFC in the clinical coagulation laboratory. Recent studies have demonstrated significant problems with the measurement of correct FVIII/IX levels following infusion of novel CF VIII/IX concentrates. The source of this problem appears to be related to the tremendous variability of the APTT reagents that are used in the one‐stage clotting assay, the most commonly used assay for determining factor levels. More specifically, the issue is related to the type of activator used in the reagents. Depending on the combination of the CFC and the APTT activator, the observed results may be either under‐ or overestimated to degrees that would be clinically relevant. Recommendations based on a review of published information regarding the potential for incorrect measurements of factor VIII/IX levels following infusion of recently developed, novel factor VIII/IX CFCs are presented for the clinician to use in clinical practice.